Stabilizing azaheptacenes - Zong, Wansheng; Hippchen, Nikolai; Zeitter, Nico; Maier, Steffen; Ludwig, Philipp; Rominger, Frank; Freudenberg, Jan; Bunz, Uwe H. F. (Journal of the American Chemical Society, 2024)
The symmetrical 7,16-diaza-6,8,15,17-tetrakis(triisopropylsilylethynyl)heptacene was obtained by a Pd-catalyzed reaction of a 2,3-diamino-1,4-diethynylanthracene with a 2,3-dibromo-1,4-diethynyl anthracene. Positioning the TIPS-ethynyl groups adjacent to the central ring suppresses dimerization via [4+4] cycloadditions and Diels-Alder reactions; the middle pyrazine ring renders this species stable to oxidation. A single crystal structure was obtained, and thin film transistors with μn = 0.042 cm2 V-1 s-1 were produced. Transposition of the alkynyl groups into the 5,8,15,18-positions with a quinoxaline unit in the center of the heptacene decreases the stability, as does the introduction of two more nitrogen atoms into the 5,18-positions. The hydrocarbon 6,8,15,17-tetrakis(triisopropylsilylethynyl)heptacene is reasonably stable with a half-life of 25 h in solution. Four correctly placed TIPS-ethynyl groups protect heptacene cores.